COMPLEX MODIFICATION OF GRAY CAST IRON - O. S. Komarov; E. V. Rozenberg; K. E. Baranowski (Литьë и металлургия)
The influence of the complex modifier by chemical – active and surface-active additives of gray cast iron on the size of chill and on the width of molted iron zone was researched. The width of a chill zone and molted iron zones were measured at chank ends of various diameter cores. The cores were casted on a massive steel plate and also in standard chill tests. It was established that additional adding of surface-active bismuth in structure of various graphitizing modifiers promoted to reduce the width a chill zone and molted iron zones. It was established that the complex modifiers consisting of chemical – active and surfaceactive components are effective in fight with chill in cast iron castings and can be recommended for application in foundry shops of the entities of a machine-building profile for production of high-quality castings.